Isolated velopalatine paralysis associated with parvovirus B19 infection - Soares-Fernandes João P.; Maré Ricardo (Arquivos de Neuro-Psiquiatria)
A case of isolated velopalatine paralysis in an 8-year-old boy is presented. The symptoms were sudden-onset of nasal speech, regurgitation of liquids into the nose and dysphagia. Brain MRI and cerebrospinal fluid examination were normal. Infectious serologies disclosed an antibody arrangement towards parvovirus B19 that was typical of recent infection. In the absence of other positive data, the possibility of a correlation between the tenth nerve palsy and parvovirus infection is discussed.